No Evidence for Moral Reward and Punishment in an Anonymous Context. - Christine Clavien; Danielle P Mersch; Michel Chapuisat (PLoS ONE, 2016)
Human social interactions are regulated by moral norms that define individual obligations and rights. These norms are enforced by punishment of transgressors and reward of followers. Yet, the generality and strength of this drive to punish or reward is unclear, especially when people are not personally involved in the situation and when the actual impact of their sanction is only indirect, i.e., when it diminishes or promotes the social status of the punished or rewarded individual. In a real-life study, we investigated if people are inclined to anonymously punish or reward a person for her past deeds in a different social context. Participants from three socio-professional categories voted anonymously for early career violinists in an important violin competition. We found that participants did not punish an immoral violin candidate, nor did they reward another hyper-moral candidate. On the contrary, one socio-professional category sanctioned hyper-morality. Hence, salient moral information about past behavior did not elicit punishment or reward in an impersonal situation where the impact of the sanction was indirect. We conclude that contextual features play an important role in human motivation to enforce moral norms.